Anionic surfactants in environmental water samples: a review - Hashim, Nor Haslina; Abu Bakar, Amnani; Awang, Zarizi; Mohd Arish, Nur Aini (Penerbit Uthm, 2018)
The complexity of environmental chemical exposure become a major concern because an essential objective of the global research effort is to improve life quality feature. Currently, environmental monitoring has become even more critical as human population increase, with the increasing strains on the environment. Surprisingly, enormous quantities of anionic surfactants (AS) are being used in households and industry every day, and most of it was end up with dispersed in different environmental compartments such as soil, water, and sediment [1].